PENGARUH PENGETAHUAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA USAHA MIKRO KECIL MENENGAH - Purnama Dewi Putu (LPSDI Bina Patria, 2023)
This study aims to determine the effect of tax knowledge and tax sanctions on taxpayer compliance in Micro Small Medium Enterprises (MSMEs) in North Denpasar registered at Denpasar Middle Tax Office (KPP Madya Denpasar). The sample of this study were 100 respondences. rThe data were analyzedrby using Multiple LineartRegression Analysis. The results show that knowledge of taxpayers, tax sanctions had a significant positive effect on taxpayer compliance. Researcher suggests KPP Madya Denpasar should pay attention to taxpayer knowledge and tax sanctions to improve individual taxpayer compliance. This means that the real increase in compulsory knowledge taxes will lead to increased taxpayer compliance on North Denpasar MSMEs that are registered at the Denpasar Middle Tax Office (KPP Madya Denpasar). In addition, increasing tax Sanctions will cause increasing taxpayer compliance in North Denpasar MSMEs registered at Denpasar Middle Tax Office (KPP Madya Denpasar).